Pollination by nitidulid beetles in the hemi-epiphytic aroid Monstera lentii (Araceae: Monsteroideae) - Prieto, Danyi (2017)
Among aroids (Araceae family) with bisexual flowers, the reproductive biology of the neotropical genus Monstera (Subfamily Monsteroideae) is misunderstood. Nothing is known about the reproductive phenology and the sparse evidence on its pollination system is equivocal, suggesting both bees and beetles as pollinators. In order to elucidate the pollination system and reproductive behavior of Monstera, we documented the floral cycle, spathe movement, floral visitors, and heat production of the inflorescence, and the flowering and fruiting phenology of M. lentii in a montane forest in Costa Rica. We found that M. lentii was mainly visited and likely pollinated by nitidulid beetles (Cychrocephalus corvinus, Nitidulidae) from the Mystropini tribe, which were mainly known as palm pollinators so far. In this mutualism, the beetles use the floral chamber as shelter, mating place, and probably as brood site. Drosophilid flies also visited the inflorescences and might participate in a mixed-pollination system, while stingless bees are considered as pollen robbers. Flowering and fruiting peaks occurred during the rainy season. Floral development was protogynous, a mechanism likely to prevent self-pollination. We concluded that pollination in M. lentii represents a highly dependent system on biotic pollinators for successful fruit set which likely contributes to an out-crossed mating system. Our findings indicate that pollination systems of bisexual aroids are more diverse than previously suggested.